Different inhibitory effect of a neuropilin-1 monoclonal antibody on different types of hepatocellular carcinoma - Yafei Zhang; Xiaofeng Dou; Jianghua Yan; Rongshui Yang; Xinhui Su (Discover Oncology)
Abstract As a co-receptor for vascular endothelial growth factor, neuropilin receptor type-1 (NRP-1) plays a crucial role in tumor angiogenesis, growth, and metastasis, and is regarded as a promising target for cancer molecular imaging and therapy. However, few data on inhibitory effect of an anti-NRP-1 monoclonal antibody on HCC with different NRP-1 expression levels have been reported. This study aimed to investigate inhibitory effect of an anti-NRP-1 monoclonal antibody (A6-11-26) on different types of HCC, with a view to further understanding the role of A6-11-26 in HCC. Three different types of HCC cell lines (Bel-7402, SMMC-7721 and HepG2) were conducted in this study. MTT, colony formation test, cell morphology, and flow cytometry were used to assess the inhibitory effect of A6-11-26 on three HCC cell lines. The in vivo growth inhibitory effect of A6-11-26 was evaluated in mice xenograft models bearing three HCC cell lines respectively. Immunohistochemistry analyses was performed to characterize the expressions of vascular endothelial growth factor receptor (VEGFR) and NRP-1 in HCC tissues after A6-11-26 administration. A6-11-26 displayed to inhibit the proliferation, migration and apoptosis of HCC cells in vitro and tumor growth in vivo. The inhibitory effect of A6-11-26 was dose-dependent and dependent on the level of NRP-1 expression. The decreasing expressions of VEGFR and NRP-1 in HCC tissues after A6-11-26 treatment had also dose-dependent and NRP-1 expression characteristics. Taken together, an anti-NRP-1 monoclonal antibody (A6-11-26) can inhibit HCC growth through decreasing NRP-1 and VEGFR expression accordingly with NRP-1 expression characteristics, suggesting that A6-11-26 may be a potential targeted medicine for HCC with high NRP-1 expression.